Evaluating zinc content in aquatic ecosystem by estimating the responses of diatom biofilm to environmental and biological variables - Lundqvist, Anders (2016)
Zinc is a common essential metal. At too high exposure it will become toxic. Diatoms have a species-specific cell wall and they are easy to collect and to preserve. When exposed to environmental stress they could have teratological form, which is one of the reasons to have diatom as a bioindicator for metal contamination assessment. However, there are many variables could influence the bioavailability of zinc and other metals for diatoms. So in this review, we will evaluate the effects of different environmental and biological variables on zinc content in aquatic ecosystems. We also suggested here to have an interactive conceptual model to better assess what is known, what should be verified and what is needed in order to be better at evaluating the effects on diatom communities of zinc exposure.